2022
DOI: 10.3390/ijms232415824
|View full text |Cite
|
Sign up to set email alerts
|

The Modular Architecture of Metallothioneins Facilitates Domain Rearrangements and Contributes to Their Evolvability in Metal-Accumulating Mollusks

Abstract: Protein domains are independent structural and functional modules that can rearrange to create new proteins. While the evolution of multidomain proteins through the shuffling of different preexisting domains has been well documented, the evolution of domain repeat proteins and the origin of new domains are less understood. Metallothioneins (MTs) provide a good case study considering that they consist of metal-binding domain repeats, some of them with a likely de novo origin. In mollusks, for instance, most MTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Evolutionarily, MTs are observed to undergo reshuffling, rearrangement, multiplication or formation of de novo domains, which provides new functional abilities, such as increasing the frequency of metal ion binding or increasing the affinity for a specific metal ion. 98 In this way LlMT increases the buffering capacity and range of buffered pZn compared to two-domain MTs. Moreover, such an evolutionary procedure in the form of increasing the size of a given protein is more energetically advantageous than gene duplication, as was proven during research on yeast.…”
Section: Resultsmentioning
confidence: 99%
“…Evolutionarily, MTs are observed to undergo reshuffling, rearrangement, multiplication or formation of de novo domains, which provides new functional abilities, such as increasing the frequency of metal ion binding or increasing the affinity for a specific metal ion. 98 In this way LlMT increases the buffering capacity and range of buffered pZn compared to two-domain MTs. Moreover, such an evolutionary procedure in the form of increasing the size of a given protein is more energetically advantageous than gene duplication, as was proven during research on yeast.…”
Section: Resultsmentioning
confidence: 99%
“…The two-domain organization is overall conserved among gastropod MTs, even though exceptions can be found. 19 , 39 The advantage of this two-domain organization is, however, less clear since both domains can act in isolation despite forming contacts in the native proteins. 20 , 39 Further, the degree to which either domain is conserved varies, with C-domains being generally more conserved among gastropod MTs.…”
Section: Resultsmentioning
confidence: 99%
“…This has led to a multiplication of the binding stoichiometry for Cd 2+ (or other divalent metal ions) in the corresponding MTs (Pedrini-Martha et al 2020 ). The capacity to form multidomain MTs seems to be an ancient character of molluscs (Jenny et al 2004 , 2016 ; Nam and Kim 2017 ; Calatayud et al 2022 ) and has also been observed in the class of bivalves and in other animal phyla, too (Calatayud et al 2018 ).
Fig.
…”
Section: The Multifarious World Of Gastropod Mtsmentioning
confidence: 99%